Investigation of the effects of steam injection on performance and emissions of a diesel engine fuelled with tobacco seed oil methyl ester - Parlak, Adnan; Ayhan, Vezir; Cesur, Idris; Kokkulunk, Gorkem (ELSEVIER SCIENCE BV, 2013)
Although biodiesel is renewable, nontoxic, biodegradable and has low emission profiles, the main drawback of using biodiesel in diesel engines is higher NOx. In this study, steam injection has been used as a method to reduce NOx emissions of a direct injection diesel engine fuelled with tobacco seed oil methyl ester (TSOME). The effects of 10% (S10) and 20% (S20) steam ratio have been investigated in terms of performance and emissions of a diesel engine fuelled with 20% (B20) TSOME. Steam is injected into the inlet manifold during inlet period. It is shown that steam injection into the engine fuelled with B20 fuel improved torque, effective power, effective efficiency and specific fuel consumption (SFC) decreased. Whilst S10 has been found optimum at the low engine speeds, S20 is optimum at the high speeds for the performance. However, S10 has been found as optimum for the exhaust emissions. At this injection ratio, both NOx and smoke emissions decrease. As a result, steam injection is a found powerful tool for reducing NOx emissions of the diesel engines running with biodiesel blend. (C) 2013 The Authors. Published by Elsevier B.V. All rights reserved.
Keywords: Diesel engine; Biodiesel; Tobacco seed oil; Steam; Performance; Emissions; EXHAUST EMISSIONS; BIODIESEL PRODUCTION; BLENDS; COMBUSTION; CATALYSTS; SYSTEM; Chemistry; Energy & Fuels; Engineering